African Academic Diaspora: Training and Research - Frittelli, Claudia (International Higher Education, 2018)
Tertiary education enrollment in sub-Saharan Africa nearly doubled from approximately 4.5 million in 2000 to 8.8 million in 2016 (UNESCO UIS). To meet the needs of new and expanding universities, several African governments aim to increase the number of doctoral graduates who can become qualified staff. African universities have deployed innovative models of academic diaspora linkages in building the next generation of academics.